Sedanje stanje gozdnih cest kot rezultat preteklega gospodarjenja - Hribernik, Boštjan (Zbornik gozdarstva in lesarstva, 2006)
Forest roads are built for forest management purposes, to which planning of their use and maintenance is adapted. The increasing importance of non-forestry use of forest roads leads to higher maintenance standard, which by formed maintenance system causes permanent shortage of funds. Higher maintenance costs occur due to the past forest roads construction characteristics, which gave priority to quick opening of villages and farms, on the account of building quality. Other funds expenditure represented by works for the finishing of road constructions occur permanently. Present forest roads condition is a result of the past road construction, road use andmaintenance. We investigated forest road conditions with inventories of damages in sample hectometre sectors. Critical apart from the upper road layerand road bed layer damages is the low level of perfection of the roads' drainage system.
Keywords: gozdne ceste; Slovenia; Slovenija; vzdrževanje cest